Digital real-time microscopy of ex-vivo tissues: A novel strategy to control surgical accuracy. Issue 1 (February 2023) - Sighinolfi, Maria Chiara; Cimadamore, Alessia; Cassani, Alessandra; Assumma, Simone; Sarchi, Luca; Filippi, Beatrice; Turri, Filippo; Reggiani Bonetti, Luca; Maiorana, Antonino; Eissa, Ahmed; Micali, Salvatore; Montironi, Rodolfo; et al.
Introduction: Ex-vivo FCM is a novel digital optical technique that provides images of fresh tissues in a real-time fashion with magnification to subcellular details of a flattened unprocessed sample. Digital images are hematoxylin-eosin-like and can be shared and interpreted remotely. In urology, FCM has been successfully applied for prostate tissue interpretation, either during biopsy and radical prostatectomy. Possible applications of FCM may reflect those of frozen section analysis and can be extended to all fields in which the intra-operative microscopical control is advisable. Materials and methods: This is an investigative prospective case series that aims to explore FCM feasibility in novel surgical settings and provide a depiction of FCM digital images in those fields. The definite purpose is to check the accuracy of surgical specimen during the following interventions: (a) trans-urethral resection of bladder tumors, to confirm the presence of muscular layer; (b) biopsy of a retroperitoneal mass, to check for the location and quality of cores; (c) training in robotic radical prostatectomy, to control surgical margins after a nerve sparing performed by a trainee. To this aim, we collected FCM images during seven surgical procedures. FCM findings were compared to those from the final histopathological analysis and the agreement was assessed. Results: In all cases, FCM digital images were obtained in the OR. FCM was able to confirm the presence of muscular layer in TURB specimen, the presence of lymphomatous tissue, surgical margins at prostate specimen. FCM intra-operative interpretation was consistent with final histopathology in all cases. Conclusions: Ex vivo FCM may represent a novel approach to control the quality of specimens, likely to tailor surgical strategy in a real-time fashion. Moreover, digitalization represents a step toward the implementation of telepathology in clinical practice.